2003
DOI: 10.1016/s0378-5173(03)00148-0
|View full text |Cite
|
Sign up to set email alerts
|

Planar gamma scintigraphy—points to consider when quantifying pulmonary dry powder aerosol deposition

Abstract: Methodological aspects of planar gamma scintigraphy used to quantify pulmonary aerosol deposition were investigated using an experimental dry powder formulation. Particles of micronized salbutamol sulphate were labelled with technetium-99m and admixed to an ordered mixture of unlabelled micronized salbutamol sulphate and larger carrier particles of lactose. The radioaerosol was administered to 24 healthy subjects, 12 in each of two consecutive, similarly designed studies. Pulmonary deposition was determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this way budesonide and fluticasone propionate plasma levels can give a good indication on tissue levels [112]. Also, for salbutamol sulfate deposition by gamma scintigraphy and plasma levels showed very similar values (26.2% vs. 26.4%) [113]. Further, it has also been shown that deposition of budesonide is linked to local action.…”
Section: In Vivo Parameters For Drug Actionmentioning
confidence: 99%
“…In this way budesonide and fluticasone propionate plasma levels can give a good indication on tissue levels [112]. Also, for salbutamol sulfate deposition by gamma scintigraphy and plasma levels showed very similar values (26.2% vs. 26.4%) [113]. Further, it has also been shown that deposition of budesonide is linked to local action.…”
Section: In Vivo Parameters For Drug Actionmentioning
confidence: 99%
“…The scattering of photons can cause distortions in scintigraphy images and lead to inaccurate dose quantification, with around 30% of photons being scattered and causing measurement errors. Other factors that can affect accuracy include the dosage administered before the study, aerosol radiolabeling quality control, and radioactivity recovery [ 27 ]. Furthermore, scintigraphy images are only 2D and cannot distinguish between multiple layers of deposition.…”
Section: Introductionmentioning
confidence: 99%